2020
DOI: 10.1111/jre.12790
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a behavioural management tool in adults with mild to moderate periodontitis. A single‐blind, randomized controlled trial

Abstract: Objective To compare a behavioural management program (test) to a standard communication approach (control) to reduce plaque, improve clinical outcomes and patient's compliance with oral self‐care. Background Since psychological factors affect oral health–related behaviours, approaches directed at changing behaviours and improving compliance might improve the effect of oral health education. Materials and Methods This was a randomized, single‐blind, parallel‐design trial involving 71 patients with mild to mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…For example, of 14 extracted teeth initially judged to have “good” or “fair” prognosis by McGuire and Nunn (1996), only 1 was extracted for periodontal reasons, while others were lost for fractures ( n = 6), crowding/orthodontic reasons ( n = 5) and caries ( n = 2). Furthermore, relying on tooth data alone in these prognostic systems is not enough to provide optimal patient care, as patient factors are also very important, and a questionable tooth in the mouth of a “good prognosis” and very motivated patient (Donos et al, 2021) can have a better prognosis than in the mouth of a non‐compliant patient with other risk factors (Eickholz et al, 2008; Morelli et al, 2017). Other studies have also tried to combine patient factors such as smoking and bruxism with tooth factors (Martinez‐Canut & Llobell, 2018) or to use the staging and grading classification in order to predict tooth loss (Ravidà et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For example, of 14 extracted teeth initially judged to have “good” or “fair” prognosis by McGuire and Nunn (1996), only 1 was extracted for periodontal reasons, while others were lost for fractures ( n = 6), crowding/orthodontic reasons ( n = 5) and caries ( n = 2). Furthermore, relying on tooth data alone in these prognostic systems is not enough to provide optimal patient care, as patient factors are also very important, and a questionable tooth in the mouth of a “good prognosis” and very motivated patient (Donos et al, 2021) can have a better prognosis than in the mouth of a non‐compliant patient with other risk factors (Eickholz et al, 2008; Morelli et al, 2017). Other studies have also tried to combine patient factors such as smoking and bruxism with tooth factors (Martinez‐Canut & Llobell, 2018) or to use the staging and grading classification in order to predict tooth loss (Ravidà et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Only one study reported the participation of a Ph.D. student in Psychology trained in MI and a clinical psychologist 24 who examined fidelity with recording audios, performance rating and feedback. In the case of Donos et al, 15 the same clinician gave both interventions previously receiving specific training and taking care to minimize the risk of crossover effect. Moreover, Stenman et al 24 reported the fidelity assessment with MI Treatment Integrity, 25 and Almomani et al 23 also mentioned that they assessed the fidelity, but it was not reported.…”
Section: Resultsmentioning
confidence: 99%
“…For BOP, the two considered effects are Jönsson et al 22 with a mean change of −4.00 (CI: [−9.78; 1.78]) and Donos et al 15 with a mean change of −10.00 (CI: [−17.78; −2.22]). The summary effect for these two studies was a mean change of −6.13 percentage points (CI: [−10.77; −1.49].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations